The Effect of Coffee on The Quantity of Spermatozoa of Diabetic Wistar Rats Inducted By Aloxan - Ahmad Alrizaldi; Riandini Aisyah; Safari Wahyu Jatmiko (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Hyperglycemia in people with diabetes mellitus causes oxidative stress which can interfere with the provision of nutrients through blood vessels to the tissues that form spermatozoa so that it interferes with the process of spermatogenesis in the testicular organs. Coffee contains caffeine and chlorogenic acid which functions as an antioxidant to improve spermatogenesis abnormalities which causes decreased number of normal spermatozoa. The purpose of this study was to determine the ability of coffee in improving the number of spermatozoa of alloxan induced wistar white rats.. Methods this study uses Post-test only laboratory experimental research with control group design. Submitting 30 rats divided into 5 groups: normal control (given aquades), negative control (induced alloxan + aquades), setting 1 (induced alloxan + coffee 0.054 gram / 200 gramBB), aid 2 (alloxan induced + coffee 0.108 gram / 200 gramBB ) and treatment 3 (alloxan + coffee induced 0.162 gram / 200 gramBB). Provision of coffee carried out for 14 days, rats terminated on the 15th day. Testicles are taken then observed and counted spermatozoa. One-way ANOVA test results show the value of p = 0.000. In the LSD test between the normal control group (aquades) and negative control (diabetic rats without treatment) had a value of p = 0.042, whereas in the treatment group 1.2.3 with a negative control had a value of p = 0.000. Provision of coffee can increase the number of spermatozoa white wistar strain alloxan induced.